Computerised scoring protocol for identification and quantification of different immune cell populations in breast tumour regions by the use of QuPath software. Issue 1 (18th June 2020) - Berben, Lieze; Wildiers, Hans; Marcelis, Lukas; Antoranz, Asier; Bosisio, Francesca; Hatse, Sigrid; Floris, Giuseppe
Abstract : Aims: As important prognostic and predictive information can be obtained from the composition, functionality and spatial arrangement of different immune cell subtypes, this study aims at characterizing the immune infiltrate in breast tumours. Methods and results: Tumour‐infiltrating lymphocytes (TILs) in 62 patients with luminal B‐like breast cancer were characterised by immunohistochemical staining with standard markers, and were subsequently classified and quantified by the use of QuPath software. In different delineated tumour regions, the proportion and density of CD3 +, CD4 +, CD5 +, CD8 +, CD20 + and FOXP3 + cells were assessed. The results of the software analysis were compared with those of manual counting for CD8 and CD20 staining. The QuPath scoring protocol slightly overestimated positive, negative and total lymphocyte counts and density, while minimally underestimating the proportion of positively stained lymphocytes. However, for density and proportion, no real differences from manual counting were observed. For all markers, the density of positively stained immune cells was higher in the invasive front than in the tumour centre, pointing to an accumulation of immune cells near the tumour boundaries. When we looked at the proportion of immunohistochemically positive immune cells, we observed enrichment of CD5 ( P  = 0.025) and CD20 ( P  < 0.001) at the periphery, and FOXP3 enrichment in the centre ( P  < 0.001). Conclusion: The QuPath scoring protocol can adequately identify positively stained immune cells in breast tumours, and allows the evaluation of differences in immune cell proportion and density within different tumour regions. The entire tumour section can be quantitatively assessed quite rapidly, which is a major advantage over manual counting.